Village Government Capability In Realizing Rural Road Infrastructure Development - Denirius Nahak; Handrianus V M Wula; Ronaldus Nurak Nurak (Universitas Muhammadiyah Makassar, 2025)
This study aims to describe and analyze the capability of the village government in realizing road infrastructure development in Forekmodok Village, Weliman District, Malaka Regency. The findings show that the village government has attempted to improve road development through participatory planning, transparent financial management, and community involvement in implementation. Despite these efforts, several challenges persist, including limited capacity of village officials, weak supervision, and unequal development across areas, particularly in Bei Mali Hamlet. The results highlight the need for strengthening governance practices so that road development can be carried out more effectively and fairly for all communities in the village.